The context of Professional and Technological Education in pandemic times: On curricular practices and the use of digital technologies - da Silva, Tatiane das Graças; Piontkovsky , Danielle; Barcellos , Adriana Pionttkovsky; Carvalho, Gabriel Domingos (Seven Editora, 2024)
This article refers to a completed research on a remarkable moment experienced throughout the Brazilian educational context: the unexpected transition from face-to-face to remote teaching, during the period of social isolation, caused by the Covid-19 pandemic. The focus of the research was directed to Professional and Technological Education, with the Federal Institute of Espírito Santo (Ifes) as the locus of the investigation, covering the movement of implementation of non-face-to-face pedagogical activities (APNPs) in the institution, in a period of remote classes and flexible return to face-to-face classes. It is, therefore, a research that seeks to problematize the implementation of these practices with emphasis on the perspectives of curricular integration and integral human formation, as well as highlights the connections that occurred between the use of digital technologies and the integrated curriculum in the context of technical courses integrated with high school. As theoretical assumptions, the ideas of authors considered as references for the study of the themes of work and education, integral human formation, integrated curriculum, Professional and Technological Education (EPT) and digital technologies applied to the school context, such as: Frigotto, Ciavatta and Ramos (2005); Mancorda (2017); Kuenzer (2002); Mill (2014); Kenski (2011); Bacich, Neto and Trevisani (2015); Pischetola (2018) and Moran (2007). The approach used in the research is qualitative, exploratory, with emphasis on research with daily life and presents as its main methodological resource the semi-structured interview. As a result of the research, it is highlighted that after the pandemic period, digital technologies began to be more used in the context of Integrated High School (EMI) courses, as well as reaffirming the need for the use of these technologies to be increasingly present in classrooms. The research thus points to the expansion of the use of Digital Information and Communication Technologies (DICT) in curricular practices, being necessary to guarantee adequate working conditions, as well as the realization of permanent teacher training processes. During the research, an educational product was also produced, consisting of a continuing education course for teachers (in E-book and MOOC formats) entitled "Digital technologies applied to Integrated High School in the context of Professional and Technological Education", with emphasis on contents, resources and procedures for pedagogical practices, seeking to collaborate with the expansion of the use of these technological tools in Integrated High School,  in addition to contributing to the integral human formation of students. DOI:https://doi.org/10.56238/sevened2024.015-011